2020
DOI: 10.1021/acsmedchemlett.9b00544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pan-SSTRs Targeted Radioligand [64Cu]NOTA-PA1 Using Micro-PET Imaging in Xenografted Mice

Abstract: 64Cu-labeled new pan-somatostatin receptors (pan-SSTRs) probe PA1 was synthesized, characterized, and evaluated by in vitro and in vivo experiments. [64Cu]­NOTA-PA1 was obtained with high specific activity, high radiochemical purity, and good stability. Cell uptake of [64Cu]­NOTA-PA1 was higher than that of [64Cu]­DOTA-TATE in MCF-7, A549, BGC823, and HT-29 cell lines. [64Cu]­NOTA-PA1 showed high binding affinity for SSTRs expressed in A549 cells. The in vivo biodistribution and micropositron emission tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…3A). Similar uptake values have been reported by Liu et al using [ 64 Cu]Cu-DOTATATE in MCF7 (0.9 ± 0.06% AD/10 6 cells) and A549 (0.81 ± 0.21% AD/10 6 ) [24]. Cell uptake studies comparing [ 52 Mn]Mn-DOTATATE and [ 52 Mn]Mn-DOTA-JR11 in AR42J cell line showed that both radiotracers exhibited a nity for SSTR2.…”
Section: Discussionsupporting
confidence: 85%
“…3A). Similar uptake values have been reported by Liu et al using [ 64 Cu]Cu-DOTATATE in MCF7 (0.9 ± 0.06% AD/10 6 cells) and A549 (0.81 ± 0.21% AD/10 6 ) [24]. Cell uptake studies comparing [ 52 Mn]Mn-DOTATATE and [ 52 Mn]Mn-DOTA-JR11 in AR42J cell line showed that both radiotracers exhibited a nity for SSTR2.…”
Section: Discussionsupporting
confidence: 85%
“…57 For 64 Cu-NOTA-PA1 formed by conjugating 64 Cu-NOTA with a pasireotide derivative (PA1), its intercellular uptake efficiency was only 3.67 AE 0.36 and 2.97 AE 0.09% at 2 h on human breast cancer (MCF-7) and human lung cancer (A549) cell lines, respectively. 58 In the case of 64 Cu-Sur-NGR2, the 64 Cu-labeled dimeric NGR (asparagineglycine-arginine) peptide based on the sarcophagine (Sur) cage, its uptake value was observed to be 0.72 AE 0.01 and 1.72 AE 0.24% upon treating on the human fibrosarcoma (HT-1080) cell line at 1 h and 2 h, respectively, after incubation. 59 We, therefore, came up with a conclusion that our designed samples, 64 Cu-QT-NPs and 64 Cu-QT-NPs/BSA, can be a promising radioisotope delivery and imaging technology platform not only because of their high labeling efficiency and excellent chemical stability, but also because of their extremely high biocompatibility and low toxicity.…”
Section: In Vitro Cytotoxicity and Cellular Uptake Studiesmentioning
confidence: 99%
“… 8 Somatostatin receptors (SSTRs) are a group of G‐protein‐coupled receptors that have been characterized in different types of cancer, including NSCLC. 9 SSTRs are found to be overexpressed in human NSCLC by radio‐labeled analogues of somatostatin 10 , 11 and therefore, it could serve as potential targets for treatment. Cytotoxic somatostatin analogues containing doxorubicin or 2‐pyrrolino‐doxorubicin have been evaluated for treatment of colorectal cancer, 12 breast cancer, 13 glioblastoma, 14 etc.…”
Section: Introductionmentioning
confidence: 99%